The most latent cladoceran in the Holarctic revealed—sinking Unapertura Sarmaja-Korjonen, Hakojärvi & Korhola, 2000 into the genus Rhynchotalona Norman, 1903 (Branchiopoda: Cladocera: Chydoridae) - van Damme, Kay; Nevalainen, Liisa (Zootaxa, 2019)
The morphology of one of the smallest chydorid cladocerans in the world, Unapertura latens Sarmaja-Korjonen, Hakojärvi & Korhola, 2000 (Branchiopoda: Cladocera: Anomopoda) is studied herein. External features and postabdomen of the adult parthenogenetic female are discussed in detail for the first time, based on an intact specimen from northern Finland. Originally described on Quaternary fossil remains, we investigate the validity of the monotypic genus Unapertura and its position within the Aloninae subfamily, in particular in relation to Rhynchotalona Norman, 1903. As a result, we rename the taxon as Rhynchotalona latens comb. nov., based on morphology. The species, a glacial relict, seems one of the rarest cladocerans in contemporary waters in Finland, yet intact specimens are clearly overlooked and recent remains in surface sediments suggest an Arctic-Alpine distribution in oligotrophic habitats in the Holarctic.